Richness of plants, birds and mammals under the canopy of Ramorinoa girolae, an endemic and vulnerable desert tree species - Campos, Valeria E; Fernández Maldonado, Viviana; Balmaceda, Patricia; Giannoni, Stella (BOSQUE, 2017)
Dominant woody vegetation in arid ecosystems supports different species of plants and animals largely dependent on the existence of these habitats for their survival. The chica (Ramorinoa girolae) is a woody leguminous tree endemic to central-western Argentina and categorized as vulnerable. We evaluated 1) richness of plants, birds and mammals associated with the habitat under its canopy, 2) whether richness is related to the morphological attributes and to the features of the habitat under its canopy, and 3) behavior displayed by birds and mammals. We recorded presence/absence of plants under the canopy of 19 trees in Ischigualasto Provincial Park. Moreover, we recorded abundance of birds and mammals and signs of mammal activity using camera traps. Our camera traps captured more than 80, 90 and 50 % of plants, birds and mammals, respectively. The coverage estimate was 83 % for birds and 89 % for mammals. Bird species richness decreased by -43 %, for every unit increase in number of stems; although richness of plants and mammals was not explained by any variable considered. Birds and mammal species invested more time in foraging than they did in moving or resting under canopies. The abundance of South American gray fox (Lycalopex griseus) increased 9 % with abundance of birds, though not with abundance of mammals. This is the first study to assess the role of R. girolae in the provision of biodiversityrelated ecosystem services; a relevant aspect because their conservation can enhance biodiversity in arid ecosystems.